32 HOLISTIC PERSON-CENTRED CARE FOR PEOPLE LIVING WITH DEMENTIA AND CO EXISTING MENTAL HEALTH ILLNESSES: A CASE FOR INTEGRATION. (25th October 2022) - Murphy, F; O'Reilly, S; Clarke, C; Kennelly, S
Abstract: Background: 65, 000 people live with dementia in Ireland, many have co-existing or emerging mental health illnesses and non-cognitive symptoms. During the COVID-19 pandemic there was a need to provide innovative solutions to service provision. As Medicine for the Elderly (MEDEL) and Psychiatry of Later Life (PLL) were established stand-alone services, there was no formalised working relationship, resulting in an overlap of cases and disparity in service provision. Methods: A description of three cases to illustrate the joint working interface with MEDEL and PLL. These cases highlight their complex care needs and the speciality input required by both services within a shared catchment area. The age range was 78-88 years. All presented with at least two medical co-morbidities, including vascular risk factors and delirium. Each had at least one mental health illness including new onset psychotic and mood disorders. Sharing of resources including diagnostic services, nursing, medical, occupational therapy, physiotherapy and social work facilitated cost effective holistic care. Results: Given the existing structures of MEDEL and PLL, it was possible to link with community partners attached to each service, allowing domiciliary visits for crisis intervention and best use of expertise from both disciplines. This resulted in the provision of timely patient centred care, reduced polypharmacy through a unified pharmacological approach, enhanced communication, shared learning and cost effectiveness. Care that is in the right place at the right time, in line with Sláinte Care, allowed timely access to diagnostics, improved care outcomes and a cohesive response. Conclusion: This cohort present with complex care needs. An integrated approach enables patients to receive holistic care without duplication of resources or disparity of treatment and care options. Going forward this should involve a fully integrated memory service, with shared governance.